Leptin affects proliferation-, apoptosis- and protein kinase A-related peptides in human ovarian granulosa cells - Sirotkin, Alexander V; Mlynček, Miloš; Makarevič, Alexander; Konýčková, Iveta; Hetényi, Ladislav (Physiological research, 2008)
The aim of our in vitro studies was to understand the role of leptin in controlling proliferation, apoptosis, and protein kinase A (PKA) in human ovarian cells. We analyzed the in vitro effects of leptin (0, 1, 10 or 100 ng/ml) on the accumulation of proliferation-related peptides (PCNA, cyclin B1), apoptosis-associated peptide (Bax) and the intracellular signaling molecule PKA in cultured human granulosa cells using immunocytochemistry and Western immunoblotting. It was observed that leptin stimulated in a dose-dependent manner the accumulation of PCNA (at doses 1-100 ng/ml), cyclin B1 (at doses 10 or 100 ng/ml), Bax (at doses 10 or 100 ng/ml) and PKA (at doses 1-100 ng/ml) in cultured human ovarian cells. These observations suggest the ability of leptin to control directly human ovarian cell functions: proliferation, apoptosis, and intracellular messenger PKA.
Keywords: leptin; folikulární buňky; financování organizované; kultivované buňky; proliferační antigen buněčného jádra; signální transdukce; Cell Cycle; cyklin B; apoptóza; imunohistochemie; rekombinantní proteiny; protein X asociovaný s bcl-2; Signal Transduction; Cell Proliferation; Adult; Leptin; bcl-2-Associated X Protein; buněčný cyklus; western blotting; Proliferating Cell Nuclear Antigen; Cells, Cultured; Blotting, Western; Immunohistochemistry; Financing, Organized; ženské pohlaví; Humans; Cyclic AMP-Dependent Protein Kinases; proteinkinasy závislé na cyklickém AMP; Granulosa Cells; proliferace buněk; Cyclin B; dospělí; Female; lidé; Recombinant Proteins; Apoptosis